2022
DOI: 10.3389/fonc.2022.957743
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication of minimal residual disease assessment by next-generation sequencing-based immunoglobulin clonality assay in pediatric B-acute lymphoblastic leukemia

Abstract: Measuring minimal residual disease (MRD) during treatment is valuable to identify acute lymphoblastic leukemia (ALL) patients who require intensified treatment to avert relapse. We performed the next-generation sequencing (NGS)-based immunoglobulin gene (Ig) clonality assay and evaluated its clinical implication in pediatric B-ALL patients to assess MRD. Fifty-five patients who were diagnosed and treated with de novo (n = 44) or relapsed/refractory B-ALL (n = 11) were enrolled. MRD assessment was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, three cases detected with positive MRD using the CD45-ROR1 panel were detected to be MRD-negative on using the ERIC eight-color panel. To validate the MRD results of two of the three samples, NGS, which is a highly sensitive method (Lee et al, 2022), was used. The results showed that both were MRD-positive.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, three cases detected with positive MRD using the CD45-ROR1 panel were detected to be MRD-negative on using the ERIC eight-color panel. To validate the MRD results of two of the three samples, NGS, which is a highly sensitive method (Lee et al, 2022), was used. The results showed that both were MRD-positive.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 3 cases presented positive MRD as detected by CD45-ROR1 panel while negative MRD detected by ERIC 8-color panel. In order to validate the MRD results, NGS, a highly sensitive method (32), was used to assess the MRD status of 2 of the 3 samples, and the results showed that both of them were MRD positive. This result further veri ed the reliability and higher sensitivity of CD45-ROR1 panel in the MRD monitoring of CLL.…”
Section: Discussionmentioning
confidence: 99%
“…NGS offers higher sensitivity and specificity than multiple PCR, making high‐resolution examinations of all rearrangement events in a sample possible. Ig clonality analysis using NGS has proven to be a sensitive tool for detecting clonality and minimal residual disease (MRD) in various lymphoid hematologic neoplasm [ 20 , 21 , 22 , 23 ]. Although NGS‐based Ig testing for clonality detection and MRD monitoring has been previously studied, to the best of our knowledge, its clinical implications and use in BMI assessment have not been described.…”
Section: Introductionmentioning
confidence: 99%